Investigation of lubricant viscosity and third-particle contribution to contact behavior in dry and lubricated three-body contact conditions - Chen, Yang-Yuan; Horng, Jeng-Haur (Frontiers in Mechanical Engineering, 2024)
The generation of third particles and the change in viscosity lead to the gradual degradation of the performance of the machine interface. The generation of third particles may come from wear debris or environmental particles, which form a three-body contact system at the contact interface. The viscosity of the lubricant will also change with the long-term operation of the components. This paper will use a three-body lubrication model to study the influence and interaction of lubricant viscosity change and the presence of third particles on the contact characteristics, including the real contact area, the particle contact area ratio, the solid load percentage, the film thickness and evolution of the lubrication regime. The results show that when the interface is in a three-body mixed lubrication regime, the dimensionless total real contact area increases with the increase of the particle size and density at the same lubricant viscosity, while the trend is opposite in the dry contact and boundary lubrication interfaces. When viscosity decreases, the three-body contact interface is more prone to entering boundary lubrication compared to the two-body contact interface, resulting in surface damage. Regardless of surface roughness, particle size, and dry or lubricated contact conditions, the turning point of contact area (TPCA) phenomenon usually occurs when the ratio of particle size to surface roughness is 0.8~1.3. Under the same ratio of particle size to surface roughness, the critical load of TPCA phenomenon increases with the increase of third particle size and surface roughness, but decreases with the increase of lubricant viscosity and particle density.